A DNA Aptamer for Cyclic Adenosine Monophosphate that Shows Adaptive Recognition. (29th August 2019) - Sharma, Suruchi; Zajac, Matthew; Krishnan, Yamuna
Abstract: As a ubiquitous second messenger, cyclic adenosine monophosphate (cAMP) mediates diverse biological processes such as cell growth, inflammation, and metabolism. The ability to probe these pathways would be significantly enhanced if we had a DNA‐based sensor for cAMP. Herein, we describe a new, 31‐base long single‐stranded DNA aptamer for cAMP, denoted caDNApt‐1, that was isolated by in vitro selection using systemic evolution of ligands after exponential enrichment (SELEX). caDNApt‐1 has an approximately threefold higher affinity for cAMP than ATP, ADP, and AMP. Using non‐denaturing gel electrophoresis and fluorescence spectroscopy, we characterized the structural changes caDNApt‐1 undergoes upon binding to cAMP and revealed its potential as a cAMP sensor. Abstract : Characterizing the conformational changes of a DNA aptamer : A DNA aptamer that binds cAMP was isolated by using SELEX. Diverse spectroscopic and electrophoretic analyses reveal its parallel G‐quadruplex conformation, as well as its adaptive recognition of high concentrations of cAMP.